2019
DOI: 10.1016/j.dib.2019.104565
|View full text |Cite
|
Sign up to set email alerts
|

Fish-Pak: Fish species dataset from Pakistan for visual features based classification

Abstract: Fishes are most diverse group of vertebrates with more than 33000 species. These are identified based on several visual characters including their shape, color and head. It is difficult for the common people to directly identify the fish species found in the market. Classifying fish species from images based on visual characteristics using computer vision and machine learning techniques is an interesting problem for the researchers. However, the classifier's performance depends upon quality of image dataset on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 3 publications
0
17
0
1
Order By: Relevance
“…Therefore, LifeCLEF15 dataset is often used to test the robustness of the proposed object detection algorithm in changing environments 60 . Fish‐Pak mainly collected the images of the body, head and scale of six different fish species through the camera to facilitate the DL models to learn clearer features, but the number of images is relatively small 61 . F4K dataset is a real‐time video dataset captured by an underwater surveillance camera in open sea 62 .…”
Section: Deep Learning Algorithms and Datasetsmentioning
confidence: 99%
“…Therefore, LifeCLEF15 dataset is often used to test the robustness of the proposed object detection algorithm in changing environments 60 . Fish‐Pak mainly collected the images of the body, head and scale of six different fish species through the camera to facilitate the DL models to learn clearer features, but the number of images is relatively small 61 . F4K dataset is a real‐time video dataset captured by an underwater surveillance camera in open sea 62 .…”
Section: Deep Learning Algorithms and Datasetsmentioning
confidence: 99%
“…It has been observed that the research on fish identification mostly deals with marine-water fish resources and only a handful of research has been executed on fresh-water fish species. Meanwhile, a few researchers utilized pre-trained CNN models for fresh-water fish image classification where a constant background was maintained for all images captured in a laboratory environment [ 24 27 ]. Although these works demonstrate satisfactory performance, further research into the effect of varied backgrounds on the performance of these deep-learning models is still required.…”
Section: Introductionmentioning
confidence: 99%
“…Although these works demonstrate satisfactory performance, further research into the effect of varied backgrounds on the performance of these deep-learning models is still required. Moreover, there is still scope for improvement in the accuracy of the small-indigenous fish classification problems [ 24 , 28 ]. Indian water bodies carry varieties of fresh-water fish species, still, we are unable to track down any research article focusing related to these species.…”
Section: Introductionmentioning
confidence: 99%
“…Fish classification was also studied in [9], where an image dataset of six different fish species was exhibited (Fish Pack). Convolutional neural networks (CNN) were used, but no further implementation details were presented in [10]. Fish recognition from underwater images poses several challenges, such as poor image quality, unexpected objects, distortion and refraction.…”
Section: Introductionmentioning
confidence: 99%